Knowledge, attitude and practice of adverse drug reaction reporting among teaching and nonteaching hospital physicians - Karande, Vitthal B.; Burute, Ramchandra B.; Puram, Nitin N.; Murthy, Mangala B.; Burute, Shreyas B.; Ramanand, Sunita J. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Knowledge, attitude and practice (KAP) analysis may provide insight into the reasons associated with reporting of adverse drug reaction. Therefore study was carried out to investigate knowledge, attitude and practice of adverse drug reaction reporting and identify factors affecting reporting of adverse drug reactions among physicians in a teaching (THPs) and non-teaching hospital/s (NTHPs). Methods: This was a questionnaire based cross sectional study. 6 items on knowledge, 3 on attitude and 1 on practice were scored and mean KAP score calculated. The score was graded as: 0-5 low, 6-8 moderate, 9-10 high. Factors influencing reporting of ADRs were studied. Chi square and student’s unpaired t test were used to study statistical significance intergroup. Results: Out of 102, 61 were THPs and 41 NTHPs. KAP scores were similar in both groups. Both groups believed in reporting all ADRs to new and old drugs. Most did not know where to obtain a form/ if an ADR monitoring centre existed in town. Most were ready to report an ADR to ADR monitoring centre while very few had actually reported. Most were unaware how and where to report. THPs seemed more concerned about being considered negligent in duty and had difficulties identifying ADRs correctly. Conclusions: Groups had moderate knowledge, attitude and practice (KAP) score but there is scope for improvement. Attitude to reporting is positive. Concerns regarding blame for negligence in duty, difficulty in identifying ADRs, how and where to report exist. There is a need to create awareness among physicians and address these factors.